2008
DOI: 10.1007/s10350-007-9125-z
|View full text |Cite
|
Sign up to set email alerts
|

Squamous-cell Carcinoma of the Anal Canal: Predictors of Treatment Outcome

Abstract: Tolerance of chemoradiation seems to be an important predictor of treatment success. Effective therapies with less acute toxicity must be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 25 publications
9
53
1
4
Order By: Relevance
“…T1 tumors of the anal canal are not subdivided further. Combined modality therapy is the current primary therapy and standard of care for anal SCC but also has associated morbidity [153]. Historically, patients with small cancers excised with clean margins have had good outcomes [150,151].…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…T1 tumors of the anal canal are not subdivided further. Combined modality therapy is the current primary therapy and standard of care for anal SCC but also has associated morbidity [153]. Historically, patients with small cancers excised with clean margins have had good outcomes [150,151].…”
Section: Site-specific Recommendationsmentioning
confidence: 99%
“…The published literature suggests that treatment breaks are associated with inferior local control and survival for anal cancer patients [10,29]. Four patients in our study had a break, receiving a median total GTV dose of 59 Gy (range, 50-61 Gy).…”
Section: Discussionmentioning
confidence: 90%
“…The authors hypothesized that the mandated treatment break negated any benefi ts of dose escalation [18]. Similarly, a recent experience from Memorial Sloan-Kettering reported that patients with prolonged treatment breaks/protracted duration of therapy were more likely to suffer disease failure, a phenomenon confi rmed in other institutional series [19]. In this respect, the role of neoadjuvant chemotherapy preceding (and delaying) "defi nitive" RT remains unanswered.…”
Section: Chemotherapymentioning
confidence: 96%